Operators Need to Know Conventional Treatment Processes. Issue 2 (8th March 2022) - Adams, Hunter; Ash, Steve; Southard, Mark
Abstract : Qualified, dedicated, and capable water treatment plant operators are responsible for providing potable, palatable water to the public 24 hours each day and 365 days each year. To do so requires operators to understand basic conventional treatment processes that are key to ensuring drinking water quality and preventing waterborne disease.